Impact of ixazomib-lenalidomide-dexamethasone therapy on overall survival in multiple myeloma patients: Analysis of the emerging-markets subgroup of the TOURMALINE-MM1 trial. - Spencer, Andrew (Wiley, 2023)
10.1002/jha2.548